PENGUASAAN KOMPETENSI MATERI KONSEP DAN PENGELOLAAN KOPERASI DENGAN PENDEKATAN SCIENTIFIC LEARNING - Setiawati, Rokhis (Dinamika Pendidikan, 2015)
Teacher implements learning process and curriculum in the point of mastering material based on the curriculum, learning method used by the teacher is less interesting so students are not fully involved in the learning. This research is to know the 5 M activities and each competence achieved by students in scientific learning approachment.This research uses qualitative descriptive method with 138 students and subject are 32 students. The discussion object is The Mastery of Learning Competence in Scientific Learning Approachment. In collecting data, the writer uses observation, documentation and interview.The research result shows that learning process in scientific learning aprroachment includes 5M in the average shows good competence including knowledge, social and spiritual competence. Daily test shows that 5 Student got 94 in the predicate of A, 10 students got 90 , 5 student got 85 and 8 student got 84 in the predicate of A-, , 2 students got 78 and 79 in the predicate of B+. Learning process in scientific learning approachment gives opportunity for students to develop their ideas, and formulates material concept and principals, giving appreciations and enough time for students to be active in learning process.Â